2019
DOI: 10.3855/jidc.11373
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Cytomegalovirus among pregnant women in Africa

Abstract: Introduction: Vertical transmission of Cytomegalovirus (CMV), resulting in congenital CMV (cCMV) infection could have disabling and potentially fatal effects on the foetus or neonate. Although primary infection probably has a higher risk of leading to cCMV, in highly seropositive populations, a significant risk of vertical transmission is thought to be due to CMV reactivation and or reinfection during pregnancy. In this narrative review, we summarise the prevalence of CMV infection and associated risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 86 publications
4
12
0
2
Order By: Relevance
“…In contrast, the seroprevalence of HCV, HTLV 1/2 and syphilis was low, suggesting low endemicity. These findings are in concordance with our earlier seroprevalence study among HIV-infected adults in Sierra Leone, as well as other studies from the wider Africa region (Patterson et al, 2019;Rao et al, 2015;Gessain and Cassar, 2012;Murphy et al, 2015;Mhandire et al, 2019;Hussen and Tadesse, 2019). As hepatitis A is primarily transmitted through the oral-fecal route, improved water and food safety practices and immunization are effective in combating the infection.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the seroprevalence of HCV, HTLV 1/2 and syphilis was low, suggesting low endemicity. These findings are in concordance with our earlier seroprevalence study among HIV-infected adults in Sierra Leone, as well as other studies from the wider Africa region (Patterson et al, 2019;Rao et al, 2015;Gessain and Cassar, 2012;Murphy et al, 2015;Mhandire et al, 2019;Hussen and Tadesse, 2019). As hepatitis A is primarily transmitted through the oral-fecal route, improved water and food safety practices and immunization are effective in combating the infection.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, overall CMV IgM seropositivity was 2.4%, with the highest seroprevalence of 11.6% in women aged 15‐ <20 years. This high seropositivity rate was comparable to those in previous studies including those of young pregnant women in India (overall 13.63% and 16.4% in the 15‐ to 25‐year age group) 9 and Africa (ranged from 0% to 15.5% through systematic review of the literature) 10 . A previous study performed in the United States using NHANES III 1998–1994 reported overall 5.3% CMV IgM prevalence in 12‐ to 19‐year‐old women 11 .…”
Section: Discussionsupporting
confidence: 87%
“…This high seropositivity rate was comparable to those in previous studies including those of young pregnant women in India (overall 13.63% and 16.4% in the 15-to 25-year age group) 9 and Africa (ranged from 0% to 15.5% through systematic review of the literature). 10 A previous study performed in the United States using NHANES III 1998-1994 reported overall 5.3% CMV IgM prevalence in 12-to 19-year-old women. 11 Overall CMV IgM seroprevalence in the present study (2.4%) was comparable to that of other studies performed in Korea, Norway and the United States.…”
Section: Discussionmentioning
confidence: 94%
“…(6) Seropositivity of CMV IgG in our study was in line with a review done in Africa, with ranges from 60% to 100%. (9) Seropositivity rates of 77.3% for IgG and 8.1% for IgM in Kenya,(7) 93% for IgG and 11.1% for IgM in Nigeria,(13) 94% for IgG and 8.5% for IgM in Tanzania(14) were comparable to our finding.…”
Section: Discussionsupporting
confidence: 85%
“…In Africa the highest prevalence of CMV IgG was estimated ranging from 72 – 97.5% (7, 8) and of CMV IgM antibodies ranging from 0-15.5%. (9) However, for several reasons CMV infection among pregnant women in Africa have been overlooked. (10) One of the main reasons for +inattention is the perception that being infected in early childhood endures immunity for subsequent infection, so maternal reactivation or reinfection during pregnancy is unlikely to cause severe congenital infection.…”
Section: Introductionmentioning
confidence: 99%